(untitled) (Research, Society and Development, 2020)
Passion and athletic satisfaction are variables of positive psychology studied in the sports context, related to performance, and investigated at the national and international levels. The objective of the study was to analyze the passion and athletic satisfaction in Brazilian college basketball athletes, seeking to compare the passion and satisfaction of the athletes according to the time of experience and performance and to correlate the variables passion and satisfaction. 60 athletes were subjects, with an average age of 22.06 (± 3.01 years) average experience of 10.13 (± 3.61 years), participants of the 2017 Brazilian University Games. The data were analyzed by Wilcoxon tests, Friedman, U of Mann Whitney and Spearman’s correlation coefficient (p<0.05). The athletes showed a predominance of harmonious passion and were more satisfied in the dimensions of training and instruction (Md = 5.67). When comparing the passion and athletic satisfaction according to the time of experience, the more experienced athletes were more harmoniously passionate (Md = 6.00) and more satisfied in the dimensions of the team’s contribution to the task and the team’s contribution to the social dimension (Md = 5.33) (p<0.05). In the comparison of passion and athletic satisfaction according to the ranking, differences were observed for the dimensions team contribution to task (p = 0.04) and team contribution to social (p = 0.03), with superior results for non-athletes medalists (Md = 5.33). Correlations between passion were observed in all dimensions of athletic satisfaction (p<0.05), except for budget and medical management (p>0.05). Brazilian college basketball athletes are harmoniously passionate with the sport and find themselves satisfied in the aspects related to the training instruction provided by the coach and in their own contribution to the team.